Civil liberties and social and environmental information transparency: A global investigation of financial institutions. Issue 1 (January 2022) - Guo, Jianan; Islam, Muhammad Azizul; Jain, Ameeta; van Staden, Chris J.
Abstract: Civil liberties enable the media, social movements, and other stakeholders to expect companies to be more transparent and forthcoming with relevant social and environmental information. Drawing on social movement theory in general, and the notion of civil liberty in particular, we analyse the availability of social and environmental information of 300 financial companies from 50 countries over a nine-year period, to investigate the influence of country-level civil liberties on the availability of social and environmental information. We find that companies headquartered in countries with high levels of civil liberties make more social and environmental information publicly available than companies headquartered in countries with low levels of civil liberties. Furthermore, an improvement in civil liberties in countries with lower civil liberties has a bigger impact on changes in the availability of social and environmental information. Our research is relevant for the ongoing concerns of social and environmental transparency initiatives by governments, NGOs, and civil rights organisations. Policy implications for countries with lower civil liberties (typical developing nations) are that if they wish to encourage more transparent corporate information, they need to strengthen their country-level civil liberties.